Chronic lead exposure and burden of cardiovascular disease during 1990–2019: a systematic analysis of the global burden of disease study - Dang, Peizhu; Tang, Manyun; Fan, Heze; Hao, Junjun (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular diseases (CVD) are the leading causes of death and disability worldwide. Lead exposure is an important risk factor for CVD. In our study, we aimed to estimate spatial and temporal trends in the burden of cardiovascular disease associated with chronic lead exposure. Methods The data collected for our study were obtained from Global Burden of Disease (GBD) study 2019 and analyzed by age, sex, cause, and location. To assess the temporal trends in burden of CVD attributable to chronic lead exposure over 30 years, we used Joinpoint regression analysis. Results In 2019, the number of lead exposure-attributable CVD deaths and disability-adjusted life-years (DALYs) were 0.85 and 17.73 million, 1.7 and 1.4 times more than those observed in 1990, respectively. However, the corresponding age-standardized rates (ASR) of death and DALY gradually decreased from 1990 to 2019, especially from 2013 to 2019. Over the last 30 years, among 21 GBD regions and 204 countries and territories, the High-income Asia Pacific and the Republic of Korea experienced the largest reductions in age-standardized DALY and death rates, while Central Asia and Afghanistan experienced the largest increases. Males and the elderly population suffered higher death rates and DALY burdens than females and the young population. Furthermore, we observed that higher socio-demographic index (SDI) regions demonstrated lower ASR of death and DALY rates. In 2019, the low and low-middle SDI regions, especially South Asia, exhibited the highest burden of CVD attributable to lead exposure. Conclusion Our study provides a thorough understanding of the burden of CVD attributable to chronic lead exposure. The findings confirm the significance of implementing lead mitigation strategies and increasing investment in CVD prevention and treatment. These measures are crucial in reducing the burden of CVD and promoting public health on a global scale.